Pelatihan Penerapan Digital Marketing Berbasis AI Untuk Menunjang Pemasaran Branding Produk Pada UMKM Roti Bakar Bandung dan Es Teh - Sutisna Sutisna; Hasim As’ari (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service aims to enhance the product branding quality of Bandung-style grilled bread and iced tea micro, small, and medium enterprises (MSMEs) to sustain their entrepreneurship. To remain competitive in today's increasingly advanced business world, these MSMEs need to implement AI-based digital marketing. The implementation of this service is carried out using methods that include direct face-to-face observation or interviews, training on utilizing AI-based digital marketing, and finally, evaluation of the results. This training is designed to help MSMEs understand the importance of improving product branding quality to expand their market share. In this digital era, the utilization of digital technology has become crucial for MSMEs to increase the efficiency of their operations. The results of the activities conducted have shown an increased understanding among MSMEs regarding the importance of utilizing digital technology, especially the use of AI to enhance their product branding. This activity is expected to help MSMEs improve their competitiveness, expand market access, and strengthen business sustainability in the digital era, enabling them to maintain their businesses and continue to grow further.